BLADDER CANCER IN PATIENTS WITH TYPE 2 DIABETES TREATED WITH PIOGLITAZONE, A COMPARATIVE STUDY - Riaz, Amna; Khan, Khurshid; Afreen, Bahjat; Kazmi, Ijaz (Journal of Ayub Medical College Abbottabad, 2018)
Background: This study was conducted to determine the frequency of bladder cancer in diabetic mellitus type II patients treated with Pioglitazone as compared with diabetic mellitus type II patients treated with other oral therapy or insulin therapy. Methods: It was a comparative; cross sectional survey in it 1,168 patients were selected from Medical and Endocrinology out-patient departments of Jinnah hospital, Lahore and a Periphery Diabetic using non-probability purposive sampling. Patients with Duration of Type 2 Diabetics more than or equals to 2 years, both male and female aged above or equal to 40 years were selected in the study. In Group A, type 2 diabetic patients taking Pioglitazones for ‰¥2yearswere selected and in group B type 2 Diabetic patients taking oral hypo-glycaemic or insulin were selected. The ethical committee of Allama-Iqbal Medical College, Lahore, approved this study. Results: Five hundred & eighty-four patients of Group A and 584 Patients of group B were selected in the study. In group A, 321 (54.97%) were male and 263 (45.03%) were female, whereas in group B 317 (54.28%) were male and 267 (45.72%) were female. Mean age of the group A patients was 47.01±8.27 years and mean age of group B patients was 58.97±8.14years. In group A mean duration of diabetes was 8.65±3.72 years and in group B the mean duration of diabetes was 10.86±4.48 years. Mean duration of Pioglitazone use was 6.92±2.28 years. Overall none of the patient was reported with the bladder cancer in the study. Conclusions: It is concluded from the study that none of the patient from either group was reported with bladder cancer haematuria and UTI. It is suggested that a randomized control trials should be conducted to single out the association of bladder cancer in patients with type II diabetes. Keywords: Diabetes mellitus; Pioglitazone; Bladder cancer; Pakistan